Nordic research on health inequalities: A scoping review of empirical studies published in Scandinavian Journal of Public Health 2000–2021 ... - Elstad, Jon Ivar; Heggebø, Kristian; Dahl, Espen (SAGE Journals, 2022)
Aims:An important task for the Scandinavian Journal of Public Health is to address health inequality topics. This scoping review characterises Nordic empirical studies within this research field, published 2000–2021 by the Scandinavian Journal of Public Health .Methods:Original empirical research studies using data from Denmark, Finland, Iceland, Norway and/or Sweden, which linked differences in health or health-related aspects to socioeconomic positions, immigrant status, family structures and/or residential areas, were included in the review. The initial search in the Web of Science article database resulted in 294 possibly relevant articles, and 171 were judged to comply with our criteria.Results:Only one study was based on qualitative data, while all others used either surveys or register data, or both in combination. A wide variety of outcomes was addressed. Most studies had a social causation design, but 16 studies analysed health-related mobility processes and four reported intervention results. The ...